Production of perfume for sinusitis from clove oil by extraction using steam distillation method - Juma’at, Nuramirah; Ahmad Nordin, Norain; Hashim, Shazana; Abd Talib, Nur Idayu; Ahmad Soberi, Nurul Aini; Mohd Adnan, Nuraisha Syazwani (Penerbit UTHM, 2020)
Essential oils are part of the aromatherapy agent to treat some diseases [1]. Essential oils are extracted from the flowers, barks, stem, leaves, roots, fruits and other parts of the plant by various methods. But some of the people do have a respiratory system problem that is an allergy to the smell from perfume [2].